Extensive Maxillary Odontomas in 2 Dogs: Diagnosis, Pathology, and Management. (December 2016) - Hoyer, Naomi K.; Bannon, Kristin M.; Bell, Cynthia M.; Soukup, Jason W.
Two immature male dogs were presented for the treatment of extensive maxillary compound odontomas. In both cases, clinical evaluation and diagnostic imaging revealed extensive lesions invading and displacing anatomical structures of the maxilla. Histopathology confirmed the diagnoses in both cases. One dog was treated with partial rostral maxillectomy, and the other dog was treated with enucleation of the cystic lining and removal of tooth-like structures through a lateral rhinotomy utilizing an intraoral approach. This report illustrates the growth potential of maxillary compound odontomas in 2 dogs and highlights their subclinical appearance and excellent prognosis despite their extensive nature.